The legal and social implication of forced marriage in Zanzibar : towards proposing Islamic family law act - Haji, Moh'd Makame (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2012)
Family law has been one of the most political and social contested issues in Muslim context. It is observed in most cases that the personal status issues particularly at State level, are not left to accord fully with Islamic law in its fullness, but are politically controlled and statutory limited. This interference raises a lot of complications in practical aspect. Marriage practices and other matters connected and ancillary to it are sometimes predominated by Common law principles or/and customs. This study focuses on the forced marriage and its implications in both legal and social aspects in Zanzibar. In local terms, some of these marriages are commonly known as ndoa za kulazimishwa, ndoa za mkeka or ndoa za kukamatiwa and are subjected to both men and women. Common to all is the practices of forcing suitors to engage in marriage without their consents or with consent obtained by force out of their voluntary will, which are among the irregularities of Islamic marriages. The rate of forced marriage practices is very high and wide spread all over the country. The study further examines the socio-legal aspects of forced marriage in Zanzibar by discussing their formalities, procedure, the legality and the problems caused. It reflects the manners to which family issues are dealt with and the law to which it is applied. In doing so, it examines the laws related to validity of marriage in the context of provisions of voluntary marriage, its compliance and abuse. Consecutively, the study demonstrates the social and legal impacts of forced marriage practices and particularly indicates social and legal issues including the legal framework of family law of Zanzibar. The foundation of analysis is made on the bases of the practices that include customs and traditions; policies, laws, Regional and International Conventions. Basic instruments for empirical and doctrinal research have been employed significantly. It also, from time to time, comparatively demonstrates relevant practices and the law as applied in other countries such as Algeria, Bahrain, India, Indonesia, Iraq, Jordan, Kuwait, Malaysia, Morocco, Oman, Qatar, Singapore, Sudan, Tunisia, UAE and others. It invites examples of the immense diversities of strategies used by those countries to promote the formation of the codified Islamic family law when is appropriate. The study further argues that the delay of codifying comprehensive family laws in Zanzibar has been the reason of irregularities of marriage practices and matters connected to it. Moreover, it contends that number of family problems in the territory have been caused by the absence of this law which in turn gave the application of all Common law, Islamic law and uncodified customs, at the same time, to obscure the whole system. Finally, it concludes that there is a need to stop irregular practices and affirm to best practices which will ensure their legality and validity. With that regard, this study proposes the Islamic Family Law Act.